Living history in the classroom : performance and pedagogy - Heuvel, Lisa L. (Emerald Publishing Limited, 2020)
Whether it's creating their own teachable moments in costume or coaching students, many educators want to use historic characters in the classroom but lack strategies and resources. The types of questions they ask are answered in Living History in the Classroom: Performance and Pedagogy by outstanding content experts with practical insights into performance, public history, and education. The conceptual framework is based on an instructional model of performance pedagogy, developed by observing outstanding historical character portrayals and analyzing them based on intent, content and action. Written by master teachers and professionals who collaborate nationwide with teachers and students, this work is designed to help educators use the powerful tools of storytelling and interpretation to make history and social studies "come alive" for K-12 students. The professionals who have contributed to this book understand the challenges of a classroom environment, either as teachers, guest artists, or administrators. All have real-world experience with teacher development programs in the disciplines of history and social studies along with recognized content knowledge.